2012
DOI: 10.1038/pr.2012.11
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium bifidum in a rat model of necrotizing enterocolitis: antimicrobial peptide and protein responses

Abstract: Necrotizing enterocolitis (NEC) is a devastating disease of premature infants. Probiotics decrease the risk of NEC in clinical and experimental studies. Antimicrobial peptides protect the gut against noxious microbes and shape the commensal microbiota, but their role in NEC remains unclear. We report that like in human ontogeny, the rat pup has low expression of Paneth cell antimicrobials, which increases rapidly during normal development. To investigate the expression of antimicrobial peptides in experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…Armogida et al (7) reported that the presence of mediators of the innate immune system in human milk, including hBD3 provided protection for the developing digestive tract of newborns. In addition, defensins induction seemed to be a common and important mechanism of probiotics treatment (8,9). Collectively, these studies suggested an important role of defensins in neonatal mucosal defense and intestinal barrier function.…”
mentioning
confidence: 86%
“…Armogida et al (7) reported that the presence of mediators of the innate immune system in human milk, including hBD3 provided protection for the developing digestive tract of newborns. In addition, defensins induction seemed to be a common and important mechanism of probiotics treatment (8,9). Collectively, these studies suggested an important role of defensins in neonatal mucosal defense and intestinal barrier function.…”
mentioning
confidence: 86%
“…Premature infants have been shown to have fewer Paneth cells with decreased function 191,199,201,202 . Multiple animal studies implicate the importance of Paneth cells in NEC pathogenesis 203,204 . Preterm infants with NEC have been shown to have normal 4 to reduced 122,205,206 numbers of Paneth cells or poorly functioning Paneth cells 202,206 , but infants recovering from NEC have been shown to demonstrate Paneth cell hyperplasia 207 .…”
Section: Physical Barriers Protecting the Gi Tractmentioning
confidence: 99%
“…44 In the rat model of NEC, B. bifidum decreases the incidence and severity of NEC, attenuates induction of IL6, attenuates induction of trefoil factor 3 and several antimicrobial peptides, improves barrier function, activates TLR2, and decreases apoptosis. 45-47 …”
Section: Mechanisms Of Actionmentioning
confidence: 99%